SHRIMP ZIRCON DATING OF THE TUYON VOLCANOES GROUP, XINJIANG, AND ITS GEODYNAMIC IMPLICATIONS - Liang T.; Luo Z.H.; Ke S.; Wei Y.; Li D.D.; Huang J.X.; Huang F. (My University, 2007)
Tuyon basin is a Cenozoic tectono-volcanic depression located in Southwest Tien Shan, Xinjiang, NW China. The volcanic rocks are mainly of basaltic composition and occur as cone dikes, lava sheets, caldera, volcanic necks and veins. Autoclastic breccia is very prevalent in lava sheets. Many deep-seated xenoliths are occurred in the cone sheets. It indicates the cone sheets are the products of primary magma. The SHRIMP dating of zircons shows age of 48.1 ± 1.6Ma of a cone sheet. The dating results of the bottom lava layer of the caldera (Sample No. A015D) can be divided distinctly into two groups: the late Archean and the early Proterozoic. The oldest age reaches 2.5Ga, which means the Tarim block basement is probably involved in the orogenic processes of Tien Shan. The zircons from upper layer of caldera (Sample No. A015E) have shown more dispersive ages (almost distributed to the overall Paleozoic except Cambrian and Devonian), recorded the evolution process of Tien Shan. The sample A-D016 is from volcanic neck, and its zircon SHRIMP ages imply a large time span, including early Proterozoic, Devonian, Permian and Triassic. The SHRIMP dating of the cone sheet suggests that the initial time of volcano activity in the Tuyon basin is in Paleogene, it is approximately the same as in north Tibet. It may be indicates the intrinsic relationship between Cenozoic intraplate orogenesis of Tien Shan and Indian-Asian continental collision. The coexistence of zircons of different genesis and formation time reveals the lithosphere of SW Tien Shan has undertaken complex evolution, and further suggests the formation of Tuyon volcano group is related to regional lithosphere delamination.
Keywords: SHRIMP; TARIM BASIN; TIBETAN PLATEAU; TIEN SHAN; TUYON VOLCANOES GROUP; VOLCANIC APPARATUS; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен